2021
DOI: 10.3390/diagnostics11050829
|View full text |Cite
|
Sign up to set email alerts
|

Forecast the Exacerbation in Patients of Chronic Obstructive Pulmonary Disease with Clinical Indicators Using Machine Learning Techniques

Abstract: Preventing exacerbation and seeking to determine the severity of the disease during the hospitalization of chronic obstructive pulmonary disease (COPD) patients is a crucial global initiative for chronic obstructive lung disease (GOLD); this option is available only for stable-phase patients. Recently, the assessment and prediction techniques that are used have been determined to be inadequate for acute exacerbation of chronic obstructive pulmonary disease patients. To magnify the monitoring and treatment of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…A patient history of AECOPD is also not suitable for assessing the risk of first-time AECOPD, and some patient records may lack information regarding prior exacerbations. Hussain et al developed a GBM prediction model that excluded a history of AECOPD, and the model achieved high discrimination performance, with an AUC of 0.96 [19]. For the framework of the present study, we adopted ML-based modeling as the basis and then incorporated various clinical features using real-world data to account for local population characteristics, and our findings indicated that the GBM exhibited the highest prediction accuracy, with an AUC of 0.83.…”
Section: Discussionmentioning
confidence: 76%
“…A patient history of AECOPD is also not suitable for assessing the risk of first-time AECOPD, and some patient records may lack information regarding prior exacerbations. Hussain et al developed a GBM prediction model that excluded a history of AECOPD, and the model achieved high discrimination performance, with an AUC of 0.96 [19]. For the framework of the present study, we adopted ML-based modeling as the basis and then incorporated various clinical features using real-world data to account for local population characteristics, and our findings indicated that the GBM exhibited the highest prediction accuracy, with an AUC of 0.83.…”
Section: Discussionmentioning
confidence: 76%
“…In recent years, successful applications of CNNs in various fields have been reported. In the field of medical imaging, CNN architectures have shown efficient results similar to or better than those of human experts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In this study, we proved that a CNN architecture can accurately detect mandibular third molars and predict paresthesia before third molar extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning has developed rapidly in recent years, making it possible to automatically extract information in the medical field, from diagnosis using medical imaging to analysis of activity and emotional patterns [ 1 , 2 , 3 ]. The deep convolutional neural network (CNN), a type of deep learning, has been widely applied to medical images due to its high performance in detection, classification, quantification, and segmentation [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study used common and important features to predict COPD prognosis. Further, the machine learning techniques that we established could provide physicians an opportunity to develop algorithms that integrated complex interaction factors to offer different possible prognoses to patients with COPD [ 38 ]. The addition of patient demographics, laboratory data, and comorbidities in this study to predict the possible outcomes of patients with COPD was successfully modeled.…”
Section: Discussionmentioning
confidence: 99%